2017
DOI: 10.2147/ijn.s136401
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced delivery of paclitaxel liposomes using focused ultrasound with microbubbles for treating nude mice bearing intracranial glioblastoma xenografts

Abstract: Paclitaxel liposomes (PTX-LIPO) are a clinically promising antineoplastic drug formulation for the treatment of various extracranial cancers, excluding glioblastoma. A main reason for this is the presence of the blood–brain barrier (BBB) or blood–tumor barrier (BTB), preventing liposomal drugs from crossing at a therapeutically meaningful level. Focused ultrasound (FUS) in conjunction with microbubbles (MBs) has been suggested in many studies to be an effective approach to increase the BBB or BTB permeability.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 48 publications
0
57
0
Order By: Relevance
“…Although the loss of free doxorubicin by capillary drainage was slightly raised, as shown in Figure 13, the modelling results showed that keeping the BBB open for a longer time effectively improved the accumulation of both the liposome-encapsulated and free doxorubicin, which could lead to better therapy. However, it is important to note that the enhancement of drug transvascular permeability is very limited when FUS is applied in isolation [31]. Therefore, the pharmacokinetics of MB must be considered in treatment design in order to achieve continuous BBBD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the loss of free doxorubicin by capillary drainage was slightly raised, as shown in Figure 13, the modelling results showed that keeping the BBB open for a longer time effectively improved the accumulation of both the liposome-encapsulated and free doxorubicin, which could lead to better therapy. However, it is important to note that the enhancement of drug transvascular permeability is very limited when FUS is applied in isolation [31]. Therefore, the pharmacokinetics of MB must be considered in treatment design in order to achieve continuous BBBD.…”
Section: Discussionmentioning
confidence: 99%
“…in which P Gd−DPTA is the transvascular permeability of Gd-DPTA, which was measured to be 2.0 × 10 −6 m/s [30] when 0.6 MPa FUS was applied. Under similar sonication conditions, the transvascular permeability of 120 nm liposomes was about 4.25 times higher than the baseline value [31]. k r stands for the BBBD recovery rate, which can be calibrated using the semi-empirical formula [32]…”
Section: Model Parametersmentioning
confidence: 99%
“…The transwell was exposed under 1.26 W/cm 2 for 60 seconds. The microbubbles that have good stability were obtained according to our previous study . Fluorescence intensity of abluminal medium was measured at 1, 2, 4, 8 and 12 hours after FUS exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Recent evaluation of a stabilized long-circulating liposomal paclitaxel (LePTX) in a mouse model of glioblastoma showed results similar to the Le-DOX studies, with a significantly improved median survival time (47 days vs 39 days, p < 0.001) compared with no treatment. 51 Again, results were not directly compared with LePTX alone, but LePTX alone failed to demonstrate significance compared with no treatment (41 days vs 39 days, p = 0.07).…”
Section: Liposome Encapsulation and Mrgfus-enhanced Drug Deliverymentioning
confidence: 96%